2011
DOI: 10.1016/j.cca.2011.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipoprotein metabolism: VLDL vs chylomicrons

Abstract: Since Zilversmit first proposed postprandial lipemia as the most common risk of cardiovascular disease, chylomicrons (CM) and CM remnants have been thought to be the major lipoproteins which are increased in the postprandial hyperlipidemia. However, it has been shown over the last two decades that the major increase in the postprandial lipoproteins after food intake occurs in the very low density lipoprotein (VLDL) remnants (apoB100 particles), not CM or CM remnants (apoB48 particles). This finding was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 110 publications
7
95
3
1
Order By: Relevance
“…VLDLsized TG fractions may contain CM remnant, VLDL remnant, and VLDL. In humans, it has been reported that approximately 80% (or more) of the remnants observed in the postprandial state constitute VLDL-remnant (apoB-100 particles) ( 35 ). However, because rodents produce apoB48-containing lipoproteins in the liver, it was diffi cult to distinguish their origin by the size of apoB.…”
Section: Discussionmentioning
confidence: 99%
“…VLDLsized TG fractions may contain CM remnant, VLDL remnant, and VLDL. In humans, it has been reported that approximately 80% (or more) of the remnants observed in the postprandial state constitute VLDL-remnant (apoB-100 particles) ( 35 ). However, because rodents produce apoB48-containing lipoproteins in the liver, it was diffi cult to distinguish their origin by the size of apoB.…”
Section: Discussionmentioning
confidence: 99%
“…triglyceride levels as an independent cardiovascular risk factor (12)(13)(14). The goal of this study was to unravel the mechanism by which plant sterols and plant stanols lower plasma triglyceride concentrations in high-fat diet (HFD) fed wild-type mice by evaluating changes in processes that result in triglyceride appearance in the circulation.…”
Section: Methodsmentioning
confidence: 99%
“…Western individuals remain in a postprandial state for most of the day (7). Consequently, repeated acute dietary stressors induced by a high-fat meal (HFM) could trigger a large increase of most risk factors for cardiovascular diseases related to obesity, such as increased circulating cholesterol, TG, and glucose (8).…”
Section: Introductionmentioning
confidence: 99%